RAGE-aptamer Attenuates the Growth and Liver Metastasis of Malignant Melanoma in Nude Mice - Nobutaka Nakamara; Takanori Matsui; Yuji Ishibashi; Ami Sotokawauchi; Kei Fukami; Yuichiro Higashimoto; Sho-ichi Yamagishi (Molecular Medicine, 2017)
Abstract Epidemiological studies have suggested a link between cumulative diabetic exposure and cancer. The interaction of advanced glycation end products (AGEs) with their receptor (RAGE) may contribute to the phenomenon. We examined the effects of DNA aptamer raised against RAGE (RAGE-aptamer) on growth and liver metastasis of G361 melanoma in nude mice. Malignant melanoma cells were intradermally injected into the upper flank region of nude mice, which received continuous administration of RAGE-aptamer (38.4 pmol/day/g body weight) or vehicle intraperitoneally by an osmotic pump up to 42 d. RAGE-aptamer significantly reduced levels of 8-hydroxy-2′-deoxy-guanosine, AGEs, RAGE, proliferating nuclear antigen, cyclin D1, vascular endothelial growth factor (VEGF), monocyte chemoattractant protein-1 (MCP-1), and CD31 and Mac-3, respective markers of endothelial cells and macrophages in tumors of nude mice, and suppressed proliferation and liver metastasis of malignant melanoma. Furthermore, RAGE-aptamer attenuated AGE-induced oxidative stress generation, proliferation, and VEGF and MCP-1 gene expression in both G361 melanoma cells and endothelial cells. The present findings suggest that RAGE-aptamer could attenuate melanoma growth and liver metastasis in nude mice by suppressing tumor angiogenesis and macrophage infiltration via inhibition of the AGE-RAGE system. RAGE-aptamer may be a novel therapeutic tool for the treatment of malignant melanoma.